(untitled) (International Journal of Educational Management, Rivers State University., 2025)
The study investigated artificial intelligence and quality service delivery in Rivers State owned universities for sustainable national development. Three purposes of the study were formulated, three research questions and three hypotheses guided the study. The correlational survey design was adopted. The population of the study was 82 teaching staff of the two Rivers State owned universities who also served as the respondents. Census sampling was used. The Artificial Intelligence and Quality Service Delivery Questionnaire (AIQSDQ) was used as the instrument for data collection. The reliability coefficient of the instrument was 0.78, 0.81 and 0.79 respectively. Data obtained were analyzed using mean and standard deviation to answer research questions whiles the Z – ration was used to test hypotheses at 0.05 level of significance. All the items on the instrument were accepted, meaning there is a significant relationship between artificial intelligence and service delivery. Thus, the recommendation of inculcating artificial intelligence in service delivery related activities was solicited.